ANALISIS ETNOGRAFI PEMBERDAYAAN MASYARAKAT DALAM PENGEMBANGAN EKONOMI KREATIF BERBASIS KEARIFAN LOKAL GEOPARK KALDERA TOBA - Tambunan, Ellyta E (Jurnal Ilmiah Akomodasi Agung, 2025)
This study analyzes local community empowerment in the development of creative economy based on Batak local wisdom in Toba Caldera Geopark using Hammersley & Atkinson's (2019) ethnographic approach. The research focuses on craft, fashion, and culinary sectors across four Batak sub-ethnic groups: Toba, Simalungun, Karo, and Pakpak. Through thick description methods and cultural domain analysis, the study reveals three main cultural themes influencing creative economy empowerment: hagabeon (prosperity through cultural preservation), marsipature huta (collective village responsibility), and parmalim na gok (wisdom-based innovation). Findings indicate that effective empowerment strategies must integrate cultural values with modern economic approaches, addressing tensions between commercialization and cultural authenticity. The study identifies community participation patterns influenced by Dalihan Na Tolu kinship structures in ulos weaving crafts, traditional motif-based fashion, and culinary practices with nauli bulung philosophy. Results recommend a culturally-grounded empowerment model that accommodates local cultural logic to achieve economic sustainability while preserving culture.